Assessment of Arf6 Deletion in PLB-985 Differentiated in Neutrophil-Like Cells and in Mouse Neutrophils: Impact on Adhesion and Migration - Jouda Gamara; Lynn Davis; Emmanuelle Rollet-Labelle; Tsunaki Hongu; Yuji Funakoshi; Yasunori Kanaho; Fawzi Aoudjit; Sylvain G. Bourgoin (Hindawi Limited, 2020)
Chemoattractant sensing, adhesiveness, and migration are critical events underlying the recruitment of neutrophils (PMNs) to sites of inflammation or infection. Defects in leukocyte adhesion or migration result in immunodeficiency disorders characterized by recurrent infections. In this study, we evaluated the role of Arf6 on PMN adhesion in vitro and on migration to inflammatory sites using PMN-Arf6 conditional knockout (cKO) mice. In PMN-like PLB-985 silenced for Arf6 fMLP-mediated adhesion to the β2 integrin ligands, ICAM-1 and fibrinogen or the β1/β2 integrin ligand fibronectin was significantly reduced. Furthermore, overexpression of wild-type Arf6 promoted basal and fMLP-induced adhesion to immobilized integrin ligands, while overexpression of the dominant-negative Arf6 has the opposite effects. Using the Elane-Cre deleting mouse strains, we report that the level of Arf6 deletion in inflammatory PMNs isolated from the dorsal air pouches was stronger when compared to naïve cells isolated from the bone marrow. In PMN-Arf6 cKO mice, the recruitment of PMNs into the dorsal air pouch injected with LPS or the chemoattractant fMLP was significantly diminished. Impaired cell migration correlated with reduced cell surface expression of CD11a and CD11b in Arf6 cKO PMNs. Our results highlight that Arf6 regulates the activity and possibly the recycling of PMN integrins, and this compromises PMN migration to inflammatory sites.